2011
DOI: 10.1111/j.1467-9450.2011.00929.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological function and past exposure to metallic mercury in female dental workers

Abstract: The aim of this study was to see if dental personnel with previous exposure to metallic mercury have later developed disturbances in cognitive function. Ninety-one female participants who had been selected from a previous health survey of dental personnel were investigated neuropsychologically within the following domains: motor function, short-term memory, working memory, executive function, mental flexibility, and visual and verbal long-term memory. The scores were mainly within normal ranges. Relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
10
1
1
Order By: Relevance
“…Recently, Hu et al (2012) observed that administration of mercury‐contaminated rice to 3 weeks old rats disturbed the spatial learning and memory in Morris water maze. Considering mercury effects for humans, only a few studies reported effects of exposure to mercury in adulthood on cognitive functions; the most of them investigate consequences of uncontrolled exposure to this metal in humans (Smith et al, 1983; Sletvold et al, 2012); or during a short exposition in rats (Hu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hu et al (2012) observed that administration of mercury‐contaminated rice to 3 weeks old rats disturbed the spatial learning and memory in Morris water maze. Considering mercury effects for humans, only a few studies reported effects of exposure to mercury in adulthood on cognitive functions; the most of them investigate consequences of uncontrolled exposure to this metal in humans (Smith et al, 1983; Sletvold et al, 2012); or during a short exposition in rats (Hu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…2012 [29] To find late developed disturbances in cognitive function of dental personnel with previous exposure to metallic mercury.…”
Section: Sletvold Et Almentioning
confidence: 99%
“…This review includes 13 studies about possible CNS effects of chronic exposure to mercury [17][18][19][20][21][22][23][24][25][26][27][28][29] and 2 studies about possible CNS effects on offspring of female dental professionals exposed to mercury during pregnancy [30,31]. All the papers compare a group of dental workers exposed to mercury proved by blood and/or urine tests with a control group.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hos de i utgangspunktet friske personene som ble undersøkt, fant vi ingen sammenheng mellom kognitiv funksjon og antatt grad av tidligere kvikksølveksponering (9). Det var imidlertid en svak sammenheng mellom visse forstyrrelser ved visuell hukommelse og kvikksølvnivåer i urin hos 28 individer der dette var målt (10).…”
Section: Forekomst Av Helseskaderunclassified